Former Yugoslav Republic of Macedonia Banking Soundness and Recent Lessons. (IMF Working Papers; Working Paper, 2000)
After several years of transition, major weaknesses in the banking and enterprise sectors remain the root cause of low growth. A large share of nonperforming assets in the portfolio of large banks, stemming from losses in the enterprise sector, has been a key impediment to financial sector development. The banking system has been crippled with low levels of intermediation, high cost of capital, severe lack of financial discipline, and poor allocation of credit. Reforms aimed at strengthening lending practices, encouraging foreign bank participation, improving bank supervision and, above all, a consolidation process that breaks away from the past are helping pave the path to economic recovery.